1996
DOI: 10.1055/s-0038-1650292
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Recombinant Factor VIIa in Continuous Infusion

Abstract: SummaryRecombinant factor Vila (rFVIIa; NovoSeven®) is a recent addition to the hemostatic alternatives for the treatment of hemophiliacs with inhibitors. A drawback in the use of rFVIIa has been its half-life of only about 2 h, which necessitates very frequent and punctual injections. We evaluated the stability of reconstituted, but not further diluted, rFVIIa in 3 infusion systems (WalkMedTM 350 and CADD®-Plus minipumps and Meddex 2001 syringe pump). The factor VII (F VII) activity was maintained for at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
0
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 8 publications
(2 reference statements)
8
121
0
2
Order By: Relevance
“…As to the mechanism of the observed decrease in FVIIa, even complete inhibition of FVIIa production cannot explain the rapid change in FVIIa levels 30 given a half-life of 6 hours for genuine FVIIa. 31 Although FVII:Ag was significantly lower in the UFH group at baseline, no change in levels of FVII:Ag occurred at times of maximal coagulation activation.…”
Section: Discussionmentioning
confidence: 94%
“…As to the mechanism of the observed decrease in FVIIa, even complete inhibition of FVIIa production cannot explain the rapid change in FVIIa levels 30 given a half-life of 6 hours for genuine FVIIa. 31 Although FVII:Ag was significantly lower in the UFH group at baseline, no change in levels of FVII:Ag occurred at times of maximal coagulation activation.…”
Section: Discussionmentioning
confidence: 94%
“…For example, the minimum dosage to achieve hemostasis is not well defined. 11,12 The two cases reported are of interest, since gross hematuria developed a few days following the administration of rFVIIa by continuous infusion, and at a time when target hemostatic levels of FVII had been achieved. In both cases, there was no apparent cause of the hematuria, such as infection or renal calculi.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, rFVIIa's short half-life requires that it should be administered every 2-4 h. Thus, the possibility of infusion was investigated by Schulman et al He found that the overall consumption of rFVIIa can be reduced by 50% compared with bolus application. 13 Nevertheless, to treat ongoing bleeding, bolus application is preferred to achieve a fast thrombin burst.…”
Section: Mode Of Action Of Rfviiamentioning
confidence: 99%